Fiqir Iske Meqabir (Love unto the Grave) - Fellman, Jack (The International journal of African historical studies, 2005)
Fellman reviews Fiqir Iske Meqabir (Love unto the Grave) by Haddis Alemayyehu and translated by David Appleyard.